Subject index - The Editors, - (Nordic Archaeological Abstracts - NAA, 1976)
In order to simplify the use of the index the detail entries have been grouped under main entries as far as possible, for example Plough under Agriculture. In most cases reference is given from a detail-entry to the main heading. In the compressed abstracts all important subjects cannot always be mentioned, consequently many entries in the index will not be found in the corresponding abstract but refer to the original publication.